2023
DOI: 10.3390/healthcare11050771
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Use and Knowledge about Tobacco Products and Their Harmful Effects among University Students in Southern Croatia

Abstract: Understanding students’ attitudes toward smoking and tobacco products is essential for effective smoking prevention interventions. This questionnaire-based cross-sectional survey aims to determine the prevalence of use and knowledge about cigarettes, heated tobacco products, and electronic cigarettes and their harmful effects among university students. The survey was conducted using a self-administered online questionnaire among 1184 students. Questions were related to the respondents’ demographic characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, the present study did not find a significant association between the level of knowledge about the adverse effects of active smoking and opinions that passive smoking from traditional cigarettes is more harmful buccally than passive smoking from HTPs. In a survey conducted by Istenic et al 17 , it was found that most respondents had good knowledge about the adverse health effects of smoking. In our study, 76.6% recognized oral cancer risks, 91.7% identified harm during pregnancy, and 93% the link between smoking and teeth issues.…”
Section: Discussionmentioning
confidence: 99%
“…However, the present study did not find a significant association between the level of knowledge about the adverse effects of active smoking and opinions that passive smoking from traditional cigarettes is more harmful buccally than passive smoking from HTPs. In a survey conducted by Istenic et al 17 , it was found that most respondents had good knowledge about the adverse health effects of smoking. In our study, 76.6% recognized oral cancer risks, 91.7% identified harm during pregnancy, and 93% the link between smoking and teeth issues.…”
Section: Discussionmentioning
confidence: 99%
“…Another challenge for the protection of public health of the whole society, and in particular among young people, is the prevention of tobacco smoking [11]. University students are at high risk of engaging in risky behaviors such as smoking and using illicit substances [10].…”
Section: Introductionmentioning
confidence: 99%